Egypt quest for eternity - Marshall, E. G., 1910- (Washington, D.C. : National Geographic Society Educational Services, 1988)
Host E.G. Marshall looks at the ancient Egyptians who spent their whole lifetime preparing for life after death. Shows how the monuments and temples they left behind celebrate the power and mystery of their civilization. Highlights the works of Ramses.
Copy available in DVD format
Keywords: Ramses II, King of Egypt; Egypt -- Antiquities; Egypt -- Civilization -- To 332 B.C